2020
DOI: 10.34197/ats-scholar.2019-0017re
|View full text |Cite
|
Sign up to set email alerts
|

Communication Training in Adult and Pediatric Critical Care Medicine. A Systematic Review

Abstract: Background: Interpersonal and communication skills are essential for physicians practicing in critical care settings. Accordingly, demonstration of these skills has been a core competency of the Accreditation Council for Graduate Medical Education since 2014. However, current practices regarding communication skills training in adult and pediatric critical care fellowships are not well described. Objective: To describe the current state of communication curricula and training… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 36 publications
1
6
1
1
Order By: Relevance
“…Previous studies have demonstrated that various communication skills training programmes are effective in improving physicians’ communication skills, similar to our study results. 39–41 However, the primary and secondary outcomes of these studies were based on a variety of healthcare professionals’ outcomes, including scales, health status, perception of the interview, perception of their behavioural change and perception of their attitude change. 39–41 To the best of our knowledge, no interventional studies of physicians have evaluated quantitative changes in basic communication skills, such as eye contact, verbal expression or physical touch.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have demonstrated that various communication skills training programmes are effective in improving physicians’ communication skills, similar to our study results. 39–41 However, the primary and secondary outcomes of these studies were based on a variety of healthcare professionals’ outcomes, including scales, health status, perception of the interview, perception of their behavioural change and perception of their attitude change. 39–41 To the best of our knowledge, no interventional studies of physicians have evaluated quantitative changes in basic communication skills, such as eye contact, verbal expression or physical touch.…”
Section: Discussionmentioning
confidence: 99%
“… 39–41 However, the primary and secondary outcomes of these studies were based on a variety of healthcare professionals’ outcomes, including scales, health status, perception of the interview, perception of their behavioural change and perception of their attitude change. 39–41 To the best of our knowledge, no interventional studies of physicians have evaluated quantitative changes in basic communication skills, such as eye contact, verbal expression or physical touch. The reason for the increase in physicians’ communication skills after this training is likely that its methodology provides a clear conceptual basis for communication skills.…”
Section: Discussionmentioning
confidence: 99%
“…This finding justifies the importance of improving ICU nurses' communication capacity to achieve the cores of the FSM and ultimately promote family-centered critical care. Previous studies on ICU communication training primarily focused on training physicians to support structured family meetings and/or end-of-life decision-making (Mendez et al, 2020;Miller et al, 2016;Scheunemann et al, 2011). Because of the nature of nursing care, not every ICU nurse attends or facilitates family meetings; thus, these types of training may not be appropriate for nurses.…”
Section: Discussionmentioning
confidence: 99%
“…As Chiarchiaro and colleagues appropriately acknowledge, their study does have some important limitations. First, like most studies of communication training in critical illness ( 17 ), this work did not measure objective improvement in learners’ skills after the hybrid-virtual training course. Second, the work was performed at a single center and led by faculty highly proficient in communication skills training; it is unclear whether training programs with less relevant experience or fewer resources would find the same degree of success.…”
mentioning
confidence: 99%